Sustainable system for supply chain management in the Malaysian manufacturing industries: a review and research direction - Moshood, Taofeeq Durojaye; Nawanir, Gusman; Fatimah, Mahmud; W. A., Ajibike (Inderscience Enterprises Ltd., 2021)
Management teams across the industry have made significant improvements in innovative supply chain infrastructure and processes, and their facilities and products have since been significantly improved in several instances. Therefore, each of these businesses has progressed well past simple marginal improvements. Nevertheless, it is essential to be able to function smoothly through deeper connections across the whole supply chain path. It is crucial to combine the market operations, resources, and expertise to accomplish the business performance across the different channel participants in a win-win situation. A total of 77 articles were actively reviewed, including 50 Scopus journals and 27 conference papers spanning from years of publication 2003 to 2020. The implementation of sustainable supply chain management (SSCM) is a fundamental enabler that may drive businesses to concentrate on addressing environmental challenges and administering social and economic gains. Implementation reveals that this principle helps enterprises to obtain improved production, reduced operational costs and lower inventories. Therefore, this research intends to explain the scope of sustainable supply chain activities and introduce a sustainable supply chain management framework that can improve Malaysian manufacturing industries.